Design of test setup for asynchronous digital signal processor - Chua, Qijing. (2009)
The demand for Digital Signal Processors (DSP) and related algorithms has propelled it to be one of the fastest growing sectors of the semiconductor industry. Current state of the art digital systems are mainly synchronous in nature, relying on a global clock for synchronization among its various subsystems. Clock skew is a serious problem for high-speed circuitry as it has significant impact on performance and stability. Asynchronous systems do not have a global clock, thus eliminating the problems of clock distribution, clock skew and reducing power dissipation. However, usage of asynchronous system is limited due to a lack of automation design tools and environment. Testing procedures that rely on global clock for synchronisation cannot be used. This poses special challenges in testing and verification.